Optimizing Control Management: The Role of Sustainability Accounting Information Systems in Singapore's Manufacturing Sector - Mardjono, Enny Susilowati; Yang, Yi-Fang; Sujipto, Jamanto; Mudzakkir, Riyan (Journal of Ecohumanism, 2025)
This study aims to find out the factors that affect the sustainability of the performance of accounting information systems with information technology as a moderation variable. This research was conducted in the Manufacturing Industry of Blue Pearls Pte Ltd using a quantitative method with primary data sources obtained from the distribution of questionnaires. The respondents in this study were selected based on the purposive sampling method of 78 employees who work using the accounting information system. Data were processed using SPSS 29. We found that employees who have personal technical skills and attend training and development as well as internal control support lead to positive sustainability for Accounting Information System performance. This research contributes to the literature and contributes managerial information about information technology to companies. The results of hypothesis testing with multiple linear regression analysis show that internal control , personal technical skills, training and development programs have a positive effect on the performance of accounting information systems (AIS). Information technology as a moderation variable cannot moderate the influence of top management support, personal technical skills, training and education programs on the performance of accounting information systems.